PHYSIOLOGICAL AND HISTOPATHOLOGICAL EFFECT OF LEAD CHLORIDE ON KIDNEY OF GAMBUSIA AFFINIS - Amal A. Al-Kshab (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to evaluate the effect of sublethal concentrations of lead chloride on physiological and histopathological studies in Gambusia affinis . A total of 500 fish were collected from the bank of the river east of Mosul city. The fish in the aquarium were divided into five groups (control, acute exposure(20,25mg/l) and chronic exposure(5,10mg/l)). The bioaccumulation of lead in acute and chronic periods of exposure showed a significant difference in values between control and treatment. The greatest level was seen in the kidney of fish treated with lead dichloride at 10 mg/l for 30 days. The level of antioxidant Glutathione has a significant decrease in different kidneys of fish treated with pbcl2 exposed to acute and chronic concentrations. The lowest decrease was seen in kidneys of fish treated with Pbcl2 at 10 mg/l for a month. At the same time, a significant increase in lipid peroxidation (malondialdehyde) level was seen in all kidney treated with PbCl2. Histological study of the kidney showed varying degrees of pathological lesions. The glomeruli in the kidney shrank, and degeneration of Bowman’s capsule. The Pb accumulation increases with increasing concentration and period of exposure. Both acute and chronic effects caused a change in the level of antioxidants and histopathological changes in kidney of the fish. Histopathological study may be a useful indicator for determining the extent of aquatic contamination. It could be concluded that the kidney changes caused by lead exposures in fish may serve as a biomarker for the contamination of sub-lethal levels of heavy metals and other anthropogenic contaminants.